Study on the effectiveness of mergers and acquisitions in the construction industry - Nur Sabrina, Mohd Khasren (2018)
This paper investigates about mergers and acquisitions in the constructionindustry. Mergers and acquisitions are the most significant and major strategy taken by many organizations. In the construction industry, mergers and acquisitions have been used to accelerate growth, entering new markets, widened the company’s client base and also as risk management. During the last few decade, every construction company tried to reduce the cost efficiently in order to minimize potentials and economic competitions. The research finds out various importance and factors that would affect mergers and acquisitions in the construction industry. The factors emphasis on the increasing income, sales of services, cost of efficiency, position in the market and branding. The research objectives are: (a) To study the importance and factors needed to consider of mergers and acquisitions in the construction industry, (b) To obtain information about mergers and acquisitions through questionnaire survey, and (c) To analyze the effectiveness of mergers and acquisitions in the construction industry. The study adopt a qualitative research methodology by distributing questionnaire to different private construction company. Similarly, Relative importance index (RII) was adopted to analyzes the data gathered from the questionnaire survey. This research provides a guideline in order to plan for a strategic mergers and acquisitions. The results of the analysis produced stated that the importance and factors had a significant relationship with the effectiveness of mergers and acquisitions and the decision to undergo mergers and acquisitions. Furthermore, this research provide a recommendation that is useful for other sectors not only construction sector if they are considering mergers and acquisitions.